Keseimbangan Kehidupan Kerja dan Burnout: Implikasinya Terhadap Kepuasan Kerja Karyawan Di You N Me Store Cirebon - Arifudin Arifudin; Khansa Firzana Busana; Mozza Juliani; Anisa Fatmauli; Khumaerahtuz Zahro (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Identifying the influence of work life balance and burnout on employee job satisfaction at You n Me Store in Cirebon City. The purpose of this study is to determine whether there is a relationship between work life balance, burnout, and employee job satisfaction at the store. Thus, this study aims to provide a better understanding of the factors that affect employee job satisfaction and how management can improve better working conditions for their employees. The type of research used in this study is an association study. Population and Sample. Data Collection Techniques, Literature review Work life balance and burnout have a significant positive influence on employee job satisfaction at You n Me Store Cirebon City. Work life balance partially has a positive and significant influence of 53.6% on employee job satisfaction. Burnout partially has a positive and significant influence of 39% on employee job satisfaction. The results of hypothesis testing show that the burnout variable partially has a significant effect on employee job satisfaction Work life balance and burnout have a positive and significant effect on employee job satisfaction at You n Me Store Cirebon City. Work life balance partially has a positive and significant effect of 53.6% on employee job satisfaction. Burnout partially has a positive and significant effect of 39% on employee job satisfaction.